A Review on Recent Techniques for Food Preservation - Kokane, Rushikesh S.; Upadhye, Chintamani R.; Husainy, Avesahemad S. N. (Asian Review of Mechanical Engineering, 2021)
Food preservation is most significant in the food industry to prevent food from the growth of bacteria and yeasts which causes spoilage of food. And also for the safety and reliability of food product, the freezing plays important role in the food industries. Modern industries has introduced many innovative food preservation freezing technologies which are explained in this review paper such freezing technologies are cryogenic freezing, air blast freezing, super-chilling, high pressure freezing and also alternate freezing processes such as ultrasound assisted freezing and electrically and magnetically assisted freezing. This freezing techniques are most commonly used to preserve the food for long period in safe manner. In this food freezing process the food is cooled from ambient temperature to chilling temperature and then stored between temperature of -18 oCand -35 oC to slow down the microbiological, physicaland chemical factorswhich are responsible for spoilage and deterioration in foods. This paper aims to accelerate the developmentand implementation of these freezing technologies by the food sector to achieve better quality and shelf life of food products.